Late Quaternary lacustrine ostracods (Ostracoda, Crustacea) and charophytes (Charophyta, Charales) from the Puna Plateau, Argentina - Palacios Fest, Manuel R. (2016)
Relatively little is known about the recent palaeontological records of the high-altitude closed basin lakes of the Central Andes, but a great need exists to remedy this knowledge gap if microfossils are to be used to infer climatic and ecological transitions from lake sediment cores. Here, eight species of non-marine ostracods and two calcareous algae are recorded from modern sediments and late Quaternary strata from Laguna de los Pozuelos, Jujuy Province, northwestern Argentina. Four species, Limnocythere alexanderi, Limnocythere foresteri, Limnocythere lysandrosi and Limnocythere ruipunctifinalis, are described as new species. Limnocythere titicaca Lerner-Seggev, 1973 has only been recorded in Lake Titicaca prior to this study and this is the first time the species is recognized outside of Bolivia. The cypridoideans Ilyocypris ramirezi Cusminsky & Whatley, 1996, Eucypris virgata Cusminsky & Whatley, 1996 and Chlamydotheca pseudobrasiliensis Martens & Behen 1994 are known species that are rare in the stratigraphic sequence in core LP06-6A. Also, the gyrogonites of two well-known species of Charophyta, Chara filiformis Hertzsch and Chara vulgaris Linnaeus, are occasionally present in the sediment from Laguna de los Pozuelos. The results provide a new vehicle for clarifying the Quaternary palaeohydrological history of the Pozuelos Basin, which is a RAMSAR wetland that is likely to be sensitive to global environmental change.